Synthesis and Characterization of SRF Fertilizer using a Mixture of Urea and Bentonite Clays - K. R. Pangestu; P. Suarya; I. A. G. Widihati (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2023)
Penggunaan pupuk nitrogen secara berlebihan mengakibatkan pencemaran lingkungan serta merusak kondisi tanah. Penelitian ini bertujuan untuk membuat pupuk slow release fertilizer (SRF) mengunakan formula campuran lempung bentonit dengan urea. Sintesis pupuk SRF mengunakan metode pencampuran padat-cair dengan mengelusikan senyawa urea ke dalam 20 g lempung bentonit dengan variasi massa urea sebesar 10, 20, 30, 40, dan 50 g. Karakterisasi terhadap hasil sintesis pupuk SRF dilakukan dengan FTIR dan metode Kjeldahl. Spektra FTIR menunjukkan adanya vibrasi dari gugus fungsi N-H, C=O, dan C-N yang menjadi penyusun pupuk urea pada bilangan gelombang 3506.59, 1691.57, dan 1176.58. Kadar nitrogen yang terkandung dalam pupuk SRF di analisis dengan metode Kjeldhal dan didapatkan kadar nitrogen tertinggi sebesar 13.35 g/100g, dengan komposisi lempung bentonit 20 g dan 50 g pupuk urea. Kata kunci: lempung bentonit, slow release fertilizer, urea. ABSTRACT Excessive use of nitrogen fertilizers causes environmental pollution and damages soil conditions. This research aimed to synthesis a slow release fertilizer (SRF) using a mixture of bentonite clay with urea. The synthesis of SRF using the solid –liquid method was carried out by eluting the urea fertilizer in the 20 g of bentonite clay with various masses of urea of 10, 20, 30, 40, and 50 g. The characterization of the SRF was done by FTIR and Kjeldhal methods. The FTIR spectra showed the presence of vibration of N-H, C=O, and C-N functional groups, which indicated the urea constituents, at the wave number of 3506.59, 1691.57, and 1176.58 cm-1. The nitrogen content in the SRF analyzed by the Kjeldhal method resulted in the highest value of 13.35 g/100g prepared with a composition of 20 g of bentonite clay and 50 g of urea fertilizer. Keywords: bentonite clay, slow release fertilizer, urea.